Peri-Implant Crevicular Fluid Analysis, Enzymes and Biomarkers: a Systemetic Review - Erhan Dursun; Tolga F. Tözüm (Stilus Optimus, 2016)
Objectives: To review the current understanding of the biomarkers and enzymes associated with different forms peri-implant diseases and how their level changes influence the pathogenesis of the inflammatory diseases around dental implants. Material and Methods: An electronic search in two different databases was performed including MEDLINE (PubMed) and EMBASE between 1996 to 2016. Human studies analyse peri-implant crevicular fluid (PICF) biomarker and enzyme levels of implants having peri-implant mucositis and peri-implantitis published in English language, were evaluated. A systematic review was performed to assess which biomarkers and enzymes in PICF were used to identify the inflammatory conditions around dental implants. Results: Fifty-one articles were identified of which 41 were further evaluated and included in the analysis. Due to significant heterogeneity between included studies, a meta-analysis could not be performed. Instead, a systematic descriptive review was performed. Conclusions: Biomarkers and enzymes in peri-implant crevicular fluid have shown promising results in differentiating from peri-implant disease condition to health. However, due to inconsistent results and acquiring much evidence from cross-sectional studies, additional evidence supported by randomized-controlled trials is needed to validate the links reported.